Long-lasting adaptive immune memory specific to SARS-CoV-2 in convalescent coronavirus disease 2019 stable people with HIV. (1st August 2022) - Donadeu, Laura; Tiraboschi, Juan Manuel; Scévola, Sofía; Torija, Alba; Meneghini, Maria; Jouve, Thomas; Favà, Alexandre; Calatayud, Laura; Ardanuy, Carmen; Cidraque, Ignacio; Preyer, Rosemarie; Strecker, Kevin; et al.
Abstract : Objective: While the course of natural immunization specific to SARS-CoV-2 has been described among convalescent coronavirus disease 2019 (COVID-19) people without HIV (PWOH), a thorough evaluation of long-term serological and functional T- and B-cell immune memory among people with HIV (PWH) has not been reported. Methods: Eleven stable PWH developing mild ( n = 5) and severe ( n = 6) COVID-19 and 39 matched PWOH individuals with mild (MILD) ( n = 20) and severe (SEV) ( n = 19) COVID-19 infection were assessed and compared at 3 and 6 months after infection for SARS-CoV-2-specific serology, polyfunctional cytokine (interferon-γ [IFN-γ], interleukin 2 [IL-2], IFN-γ/IL-2, IL-21) producing T-cell frequencies against four main immunogenic antigens and for circulating SARS-CoV-2-specific immunoglobulin G (IgG)-producing memory B-cell (mBc). Results: In all time points, all SARS-COV-2-specific adaptive immune responses were highly driven by the clinical severity of COVID-19 infection, irrespective of HIV disease. Notably, while a higher proportion of mild PWH showed a higher decay on serological detection between the two time points as compared to PWOH, persistently detectable IgG-producing mBc were still detectable in most patients (4/4 (100%) for SEV PWH, 4/5 (80%) for MILD PWH, 10/13 (76.92%) for SEV PWOH and 15/18 (83.33%) for MILD PWOH). Likewise, SARS-CoV-2-specific IFN-γ-producing T-cell frequencies were detected in both PWH and PWOH, although significantly more pronounced among severe COVID-19 (6/6 (100%) for SEV PWH, 3/5 (60%) for MILD PWH, 18/19 (94.74%) for SEV PWOH and 14/19 (73.68%) for MILD PWOH). Conclusions: PWH develop a comparable short and long-term natural functional cellular and humoral immune response than PWOH convalescent patients, which are highly influenced by the clinical severity of the COVID-19 infection.